2016
DOI: 10.1080/15622975.2016.1208844
|View full text |Cite
|
Sign up to set email alerts
|

Manic symptom severity correlates with COMT activity in the striatum: A post-mortem study

Abstract: Objectives The enzyme catechol-O-methyl transferase (COMT), which catalyzes the degradation of dopamine and norepinephrine, is posited to participate in the pathophysiology of bipolar disorder (BD) and schizophrenia. In support of this notion, rich evidence has documented that the severity of various BD and schizophrenia symptoms is moderated by rs4680, a single nucleotide polymorphism of the COMT gene featuring a valine (Val)-to-methionine (Met) substitution that results in lower catalytic activity. Neverthel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Also this allele was associated with violent suicidal attempts among schizophrenic patients ( 59 ). A study found a high correlation between COMT activity and severity of maniac symptoms in patients suffering from bipolar disorder ( 60 ).…”
Section: Catecholaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also this allele was associated with violent suicidal attempts among schizophrenic patients ( 59 ). A study found a high correlation between COMT activity and severity of maniac symptoms in patients suffering from bipolar disorder ( 60 ).…”
Section: Catecholaminesmentioning
confidence: 99%
“…Also this allele was associated with violent suicidal attempts among schizophrenic patients (59). A study found a high correlation between COMT activity and severity of maniac symptoms in patients suffering from bipolar disorder (60). Dopaminergic circuits located in the meso-corticolimbic system are involved in the executive functions that generate aggressive behavior (61).…”
Section: Catecholaminesmentioning
confidence: 99%